Eco-Brand and Customer-Based Brand Equity: Shaping Consumer Purchase Choices - Solehati*, Aisyah; Pramuditha, Panji; Rahma, Saura Jeane Aquar (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This research aims to determine the influence of eco-branding and brand equity on purchasing decisions for eco-friendly products. This research uses quantitative sampling using the Slovin technique of 100 respondents. The method in this research uses descriptive and verification analysis which is processed using the SPSS V23 program. Judging from the descriptive analysis, it can be seen that eco-branding and brand equity in purchasing decisions are in a good category. Then, through verification analysis, it is stated that there is a partial positive influence of eco-branding and brand equity. With the development of the Eco-brand introduced, the company creates Green Trust in consumers to facilitate product purchasing decisions. Not only consumers but employees are also expected to be involved by representing the company to have a reciprocal impact on society and continue to be responsible for the environment. Keywords: Eco-Branding; Brand Equity; Purchasing Decisions; Eco-Friendly; Green Trust